P359Inhibition of phosphoinositide 3-kinase gamma protects against chemotherapy-induced heart failure. (15th July 2014) - Li, M; Ghigo, A; Cimino, J; Franco, I; Morello, F; Hirsch, E
Abstract: Purpose: Phosphoinositide 3-kinase γ (PI3Kγ) signaling is pivotal in the regulation of myocardial contractility and remodeling. We demonstrated previously that inhibition of PI3Kγ lipid kinase activity limits cardiac inflammation and improves contractile function in pressure overload-induced heart failure. Here we intend to investigate whether PI3Kγ inhibition is beneficial in chemotherapy-induced cardiomyopathy. Methods: Mice expressing a kinase inactive PI3Kγ (PI3Kγ kinase-dead; KD) and wild-type controls (WT) were injected with a cumulative dose of 12 mg/kg doxorubicin (DOX) or vehicle, via 3 weekly injections (4 mg/Kg i.p. at 0, 7 and 14 days). To evaluate the effect of PI3Kγ pharmacological inhibition, a group of WT mice was pre-treated with 10 mg/Kg AS-605240, a selective PI3Kγ inhibitor, before each DOX injection. Heart morphometry and function were assessed by echocardiography 8 weeks after the first DOX injection. TUNEL assay, Picrosirius Red staining and RTqPCR were performed to assess cardiomyocyte apoptosis and collagen deposition. Immunohistochemistry, Western blot and RTqPCR were used to investigate early signaling events (6 hours and 3 days) after DOX. Results: DOX-induced cardiac cachexia was significantly reduced in KD mice as evidenced by preserved heart weight to tibial length ratio and maintained left ventricular wall thickness. In keeping with these findings, DOX-induced apoptosis was 25% lower in KD than in WT hearts (% TUNEL positive nuclei WT DOX: 36.93±3.13; KD DOX: 28.96±1.87, *P<0.05). In addition, transcriptional activation of the pro-fibrotic genes CTGF and TGF-β, as well as collagen deposition were diminished in KD hearts (% Fibrosis WT DOX: 5.24±0.33; KD DOX: 2.9±0.24, ***P<0.001). Pharmacological inhibition of PI3Kγ with AS-605240 reduced cardiac wasting, improved systolic function and survival in DOX-treated WT mice (% Fractional Shortening WT DOX: 23.4±3.7; KD DOX: 38.9±1.9, *P<0.05). The protective effects of genetic and pharmacological inhibition of PI3Kγ did not correlate with reduced inflammation as leukocyte recruitment did not differ significantly between WT, WT+AS and KD groups at 3 days after DOX. Conversely, DOX-induced autophagy was more pronounced in KD hearts than in WT controls as evidenced by increased LC3II to LC3I ratio, a marker of autophagosomal formation, and decreased expression of the autophagy substrate p62. Conclusion: Altogether, these findings demonstrate that PI3Kγ inhibition protects against chemotherapy-induced cardiac dysfunction, likely by promoting protective autophagy and the ensuing cardiomyocyte survival.